Adaptive Meshless Local Petrov-Galerkin Method with Variable Domain of Influence in 2D Elastostatic Problems - Pamuda Pudjisuryadi (Institute of Research and Community Outreach - Petra Christian University, 2008)
A meshless local Petrov-Galerkin (MLPG) method that employs polygonal sub-domains constructed from several triangular patches rather than the typically used circular sub-domains is presented. Moving least-squares approximation is used to construct the trial displacements and linear, Lagrange interpolation functions are used to construct the test functions. An adaptive technique to improve the accuracy of approximate solutions is developed to minimize the computational cost. Variable domain of influence (VDOI) and effective stress gradient indicator (EK) for local error assessment are the focus of this study. Several numerical examples are presented to verify the efficiency and accuracy of the proposed adaptive MLPG method. The results show that the proposed adaptive technique performs as expected that is refining the problem domain in area with high stress concentration in which higher accuracy is commonly required.